A simple method for squeezing juice from rice stems and its use in the high-throughput analysis of sugar content in rice stems. (2nd April 2016) - Okamura, Masaki; Hashida, Yoichi; Hirose, Tatsuro; Ohsugi, Ryu; Aoki, Naohiro
Abstract: Sugar content in rice ( Oryza sativa L.) stem is an agronomically important trait for rice used in straw silage or whole-crop silage. However, the mechanisms underlying sugar accumulation in rice stems remain unclear, mainly due to the time-consuming method for measuring sugar content. Here, we established a simple method for squeezing stem juice from rice plants, similar to that used during breeding selection in sugarcane or sorghum. The Brix value of the stem juice, which can easily be measured using a portable refractometer, significantly correlated with the soluble sugar contents in the stem juice and tended to correlate with those in stem tissues. This indicates that the Brix value of the stem juice can be used for estimating the sugar content in rice stems. This simple estimation method will be a useful tool for high-throughput analysis of sugar content in rice stems during mutant screening, QTL analysis, and breeding selection.